Local to continent-scale variation in fitness and heritability in common bean (Phaseolus vulgaris) cultivars - MacQueen, Alice H.; Khoury, Colin K.; Miklas, Phillip N.; McClean, Phillip E.; Osorno, Juan M.; Runck, Bryan C.; White, Jeffrey W.; Kantar, Michael; Ewing, Patrick M. (Wiley, 2022)
Selection during plant domestication and improvement often decreases genetic variation, including variation that confers adaptation to local conditions. We report spatial and temporal variation in fitness (seed yield), local adaptation, and segregating genetic variation within three races of common bean (Phaseolus vulgaris L.) with differing domestication histories and genetic diversities. Three‐hundred and twenty‐seven common bean genotypes had seed yield measured at subsets of 70 sites across North America between 1981 and 2015, as part of the Cooperative Dry Bean Nursery (CDBN). We estimated local adaptation using the metric home field advantage (HFA) and segregating genetic variation using heritability. The Durango and Mesoamerican races (Middle American genepool) had higher‐than‐expected (p = .002) HFA, equal to up to 34 yr of average yield gains. Surprisingly, Nueva Granada (Andean genepool) and Durango yields became more heritable across the study period (p < .001), while Mesoamerican heritability decreased (p < .001). Both metrics detected diversity loss corresponding to the timings of major historical gene introgressions. Local adaptation remains an agronomically important phenomenon within some common bean races. Common bean adaptation to new conditions will be most rapid at locations with large local adaptation benefits and high heritability.